The Philippine Neurological Association epilepsy questionnaire for community survey a validation study - Navarro, Jose
Objective: To validate the questionnaire for epilepsy as formulated by the councils of the Philippine Neurological Association. Design: Standard criterion study. Setting: The Clinical Neurophysiology Laboratory of the University of Santo Tomas Hospital (STUH). Study Population: a total of 96 consecutive patients referred to the STUH Neurophysiology Laboratory for ekectroencephalography (EEG) were included in validating thevepilepsy questionnaire. Measurements: The Philippine Neurological Association (PNA) questionnaire (6 questions) for epilepsy was administered to 96 consecutive patients and subjects who underwent EEG. The following questions were asked: 1. nawawalan ng malay? 2. natutulala? 3. naninigas or nangingisay ang buong katawan o bahagi ng katawan? 4. tumutumba? 5. nag-iiba ang kilos o ugali? 6. walang malay na pag-ihi o pagkagat ng dila? The Kappa agreement level between two neurologists was obtaibed and this was subsequently used as the gold standard in the diagnosis of epilepsy. The sensitivity and specificity of the questionnaire was then compared against a gold standard, which is the clinical diagnosis of two certified neurologists. Subsequently a multiple logistic regression analysis was performed to determine the cutoff probability of predicting the presence of epilepsy. Results: Fifty subjects with and without epilepsy were utilized to establish the Kappa agreement level of two neurologists which was intended as the gold standard in the diagnosis of epilepsy. It was shown that there is an excellent agreement (kappa=0.92) between the two neurologists. The individual question in the questionnaire was utilized in 96 subjects and had shown a sensitivity of 48-87% and specificity of 60-87%. The sensitivity and specificity of question no. 3 when administered to the guardians has shown to bew 100% and 85% respectively. Multiple regression analysis has shown that 3 questions (questions 1,3 nd 5) have significant correlation in predicting epilepsy; however one of the questions (question 4) that did not show statistical significance was forced in the model. Four questions (Question nos. 1,3,4 and 5) have shown to predict the presence of epilepsy. Utilizing 4 questions in the model and a cutoff probability of 0.65, the combination of affirmative response has shown a 67-99.3% probability of predicting epilepsy. The area under the ROC curve was 0.9312. The sensitivity and specificity of the combination of questions (OR) was also computed and the values obtained did not show a better performance. The likelihood ratio for a positive test is 5.25 and 0.19 for a negative test. The questionnaire also satisfies the User's Guide criteria for validating the results of the test. Conclusion: The PNA questionnaire for epilepsy has been shown to have a probability rate of predicting the presence of epilepsy at 67-99.3%. It has a positive likelihood ratio of 5.25 and a negative likelihood ratio of 0.19. If one would wish to get a better pick up rate from the clinical standpoint, administering the 4 questions in the questionnaire should be carried out, however for survey, such as in nation-wide detection of epilepsy administering only question no.3 (naninigas o nagingisay ang buong katawan o bahagi ng katawan) would be much simpler and practical. Recommendations: Utilizing the 4 questions which have shown statistical significance by multiple logistic regressions, we would therefore recommend it to predict the presence of epilepsy for a better clinical correlation, and for a community or nation-wide survey it will be more simple and practical to administer only question no.3.
Theses--(Master in Science in Epidemiology-Clinical Epidemiology) UPCM
Keywords: Epilepsy; Philippine Neurological Association